THE EFFECTIVENESS OF WATCHING ENGLISH MOVIES IN AUTONOMOUSLY BUILDING ENGLISH VOCABULARY AMONG AHMAD DAHLAN UNIVERSITY STUDENTS - Harnani Fatmawati; Muksin; Rina Febriana (Mutiara Intelektual Indonesia Press, 2024)
In today's dynamic job market, continuous learning and skill development are crucial for sustaining employment and enhancing career prospects. This study evaluates the implementation of upskilling and reskilling training in a culinary skills program using the Kirkpatrick Model. The Kirkpatrick Model, a widely recognized framework for training evaluation, encompasses four levels: reaction, learning, behavior, and results. This research aims to provide a comprehensive assessment of the training program's effectiveness and its impact on participants' performance and career progression. The study employs a mixed-method approach, combining quantitative surveys and qualitative interviews to gather data from participants who completed the culinary skills program. The first level of the Kirkpatrick Model, reaction, measures participants' satisfaction and engagement with the training. The second level, learning, assesses the knowledge and skills acquired during the program. The third level, behavior, examines the application of learned skills in the workplace. The fourth level, results, evaluates the overall impact of the training on participants' job performance and career advancement. The results of this evaluation indicate that the upskilling and reskilling training program in the culinary skills program was highly effective across all four levels of the Kirkpatrick Model. Participants responded positively to the training, acquired significant new knowledge and skills, applied these skills effectively in their work, and contributed to improved organizational performance.